A panchromatic spatially resolved analysis of nearby galaxies – I. Sub-kpc-scale main sequence in grand-design spirals. Issue 3 (18th February 2020) - Enia, A; Rodighiero, G; Morselli, L; Casasola, V; Bianchi, S; Rodriguez-Muñoz, L; Mancini, C; Renzini, A; Popesso, P; Cassata, P; Negrello, M; Franceschini, A
ABSTRACT: We analyse the spatially resolved relation between stellar mass ( M ⋆ ) and star formation rate (SFR) in disc galaxies (i.e. the main sequence, MS). The studied sample includes eight nearby face-on grand-design spirals, e.g. the descendant of high-redshift, rotationally supported star-forming galaxies. We exploit photometric information over 23 bands, from the UV to the far-IR, from the publicly available DustPedia data base to build spatially resolved maps of stellar mass and SFRs on sub-galactic scales of 0.5–1.5 kpc, by performing a spectral energy distribution fitting procedure that accounts for both the observed and obscured star formation processes, over a wide range of internal galaxy environments (bulges, spiral arms, and outskirts). With more than 30 000 physical cells, we have derived a definition of the local spatially resolved MS per unit area for discs, log (ΣSFR ) = 0.82log (Σ* ) − 8.69. This is consistent with the bulk of recent results based on optical IFU, using the H α line emission as an SFR tracer. Our work extends the analysis at lower sensitivities in both M ⋆ and SFR surface densities, up to a factor of ∼10. The self-consistency of the MS relation over different spatial scales, from sub-galactic to galactic, as well as with a rescaled correlation obtained for high-redshift galaxies, clearly proves its universality.